Returning Home: The Ambivalent Assyrian Experience in Turkey - BarAbraham, Abdulmesih (Poligrafi, 2021)
Discrimination and precarious living conditions in Tur Abdin, in southeastern Turkey, prompted Assyrians, indigenous Christian ethnic people to the country, to leave their homeland for Europe in the early 1960s. The process of migration continued for several decades and intensified with the militarization of the eastern provinces during the fight against the Kurdish PKK. Many Assyrian villages had to be abandoned. With an appeal formulated in a circular letter by Turkey’s then Prime Minister Bülent Ecevit in 2001, the Turkish government encouraged Assyrians abroad to return to their former homeland, assuring them that their security and rights as citizens would be guaranteed by the state. At the beginning of the new millennium, the situation in Tur Abdin seemed noticeably improved. The end of the state of emergency in the eastern provinces and the application of rule of law in the wake of the reforms in the context of EU accession process contributed to this. Many of the Assyrians who emigrated re-visited their former villages, but also tried to rebuild churches and their mostly dilapidated houses. Clarification of ownership of land and properties after occupation and changes of legal basis became a key issue.